MANFAAT MEDIA DALAM PEMBELAJARAN - Isran Rasyid Karo-Karo; Rohani Rohani (AXIOM : Jurnal Pendidikan dan Matematika, 2018)
Media is a tool or means as an intermediary to deliver lessons from teachers to students. Types of educational media commonly used are: graphics media, three-dimensional media, and media projection. Benefits of media in learning are: (1) Submission of subject matter can be uniformed. (2) The learning process becomes more clear and interesting. (3) The learning process becomes more interactive. (4) Efficiency in time and effort. (5) Improve the quality of student learning outcomes. (6) Media allows the learning process can be done anywhere and anytime. (7) The media can foster a positive attitude of students to the material and learning process. (8) Changing the role of teachers in a more positive and productive direction.